A review of power converter topologies with medium/high frequency transformers for grid interconnection systems - Nasir, Usman; Rivera, Marco; Toleda, Sergio; Costabeber, Alessando; Wheeler, Patrick (2016)
In recent years, power electronics has evolved dra¬matically due to their importance in power extracted manage¬ment from renewable sources. In this paper an overview of grid interconnection systems with galvanic isolation is presented. The most common used topologies from AC/AC, AC/DC, DC/AC and AC/AC conversion are analyzed y summarized in order to provide a good understanding of the existing technologies.